PELATIHAN KADER POSBINDU DALAM PENATALAKSANAN PENDERITA DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS MERDEKA Dan SATU ULU - Rumentalia Sulistini; Devi Mediarti; Syokumawena Syokumawena (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Diabetes Mellitus sufferers around the world are increasing every year so this requires special attention from the public. The results of the registration of cadres stated that there were still many DM sufferers who did not carry out routine control while the existing cadres had not received training in managing DM, especially Physical Exercise. Community service activities have been carried out in three stages, namely preparation, training and assistance for cadres. The target of posbindu cadres in the working area of Puskesmas 1 Ulu and Puskesmas Merdeka were 29 people. The results of the activities included the availability of training media, increased cadre knowledge and the implementation of home visits. The importance of this activity requires continuous training or refresher of cadres so that the quality of life for diabetics increases.